Were the early Firaq extremists? rethinking the history of Muslim disagreement(s) - Awang Abd Rahman, Amilah; Abdul Rahim, Adibah (University of Management and Technology, 2020)
Many writers have associated contemporary manifestations of extremism with early Islamic sects whose conclusion is argued against by this article. This study employs a critical analysis of available sources and argues for additional scrutiny. Our position is supported by detailed minutiae concerning significant circumstances and early sectarian contributions to the development of Islamic thought. We discovered remarkable limitations in the tracing of the root to the early firaq (sects) due to a strong reliance on secondary sources that are muddled in the complexities of dogmatic polemics. Nonetheless, relevant historiography improved our view of what actually happened when nascent Muslims confronted humorless political and social problems. Rather than producing extremist deviants, early Islamic thought was exceedingly dynamic and governed by a pressing need to defend sound Islamic principles. Early Muslims sought answers to perennial issues and did much to stimulate subsequent Muslim philosophy and thought. Indeed, any negative understanding of this early legacy undermines the dignity of that era and people.